Investigating the adoption of integrated STEM education within classrooms. (c2018) - El-Sayegh, Nour Adel (2018)
Education is facing, in the 21st century, various global challenges such as climate change and pollution. Solutions to these problems require the integration of science, technology, engineering and mathematics (STEM). Driven by the need to promote a society that is literate in these fields, STEM education is gaining more popularity. This case study investigated the implementation of integrated STEM education by homeroom teachers in elementary classes in an American-education private school in Beirut. Thirty homeroom teachers, three coordinators and the director of teacher professional development office participated in the study. Observations were carried out during the implementation of two instructional units in grade-3 and grade-4 classrooms. Ten semi-structured interviews were conducted with the director, coordinators, grade-3 teachers and grade-4 teachers. All homeroom teachers from the remaining grade levels were surveyed. The findings revealed that the most frequently used strategies among teachers are student-centered approaches and inquiry-based methods. Less use is made of project-based learning and model construction. Technology is used as both, a tool for teaching and learning and as a resource to find activities. Teachers reported various types of support that they get from the school administration for enhancing their technological and pedagogical content knowledge (TPACK), including collaboration, coaching, professional development opportunities and different types of resources. In addition, different external and internal barriers were identified. External barriers include lack of vision, lack of space, financial barriers, curricular issues, lack of support and time constraints. Internal barriers include personal challenges, insufficient technological and content knowledge and insufficient teacher understanding of STEM education. Although this study is limited to one elementary school, the identified themes may be useful for other schools that intend to go into STEM, as it informs educators about the challenges they may face, so they may remedy the problems and barriers at the right time.